Mekanisme Pengisian Kekosongan Jabatan Kepala Daerah Dalam Perspektif Fiqh Siyasah Serta Hukum Positif - Dewi, Amelia Kusuma (El-Dusturie, 2024)
The writing of this scientific article discusses filling vacancies in regional head positions, such as this year where there are several vacancies in regional head positions because their terms of office have expired or they have died and been dismissed for some reason, therefore there is a mechanism for appointment of regional heads (Pj) carried out by the central government. . The polemic regarding the appointment of regional heads (Pj) which is not transparent and not participatory is very inadequate because it only involves the governor, minister of home affairs and the president without considering the Constitutional Court's decision which in its legal considerations outlines that the filling of acting regional heads must be transparent and not ignore democratic values to avoid abuse of authority in the process of appointing the acting regional head. From the results of this research, it can be concluded that filling vacancies through the position appointment (Pj) mechanism is not in accordance with democratic principles because it does not involve the people either directly or through representatives in the appointment. Keywords: Vacancies in Positions, Regional Heads, Fiqh Siyasah, Positive Law